Feeding the expanding world population : international action to avert the impending protein crisis : report to the economic and social council of the advisory committee on the application of science and technology to development - United Nations (New York : United Nations, 1968)
This is a report by the advisory committee on the application of science and Technology to development proposes a series of fourteen specific measures which will require increased expenditures on the part of members of the United Nations family as well as of bilateral agencies and Governments.
Includes bibliographical references p. 98-105
hza 29/01/2019
Loans
Keywords: Food supply